Development of an e-book based on the Integrated PBL Model of Aceh Tarek Situek Local Wisdom to Improve Problem Solving Skills and HOTS Abilities of High School Students (Journal of Science Learning, 2026)
This development research uses the Research and Development method. In the development stage uses the 4D model, which consists of 4 stages, namely define, design, develop, and disseminate. The limited trial subjects consisted of 26 class XI MIPA 1 students at SMAN 1 Baitussalam. The subjects of the field trial in the experimental class 2 consisted of 30 students of X MIPA 1 and the experimental class 1 consisted of 25 students of X MIPA 3, the control classes consisted of 25 students of class X MIPA 4 at SMAN 1 Baitussalam. The data collection instruments included student response questionnaire assessment sheets, problem-solving skills assessment sheets and HOTs abilities. The validity of the lesson plan, student response questionnaire, product assessment used a Likert scale, while the validity of the instrument used v Aiken. The validity and reliability of the student assessment instrument used the Quest Application. Data analysis using MANOVA test, namely using Hotelling's T2 multivariate analysis with a significance level of 0.05. The results of the study in the form of Development of e-books Based on the Integrated PBL Model of Tarek Situek Local Wisdom: (1) e-books based on the integrated PBL model of Aceh Tarek Situek local wisdom are feasible and practical for use in Physics learning (2) e-books based on the integrated PBL model of Aceh Tarek Situek local wisdom are effective for improving problem-solving skills and HOTS abilities of high school students